Pengaruh ukuran perusahaan, leverage, dan profitabilitas terhadap nilai perusahaan - Agustiningsih, Wulandari; Septiani, Natasya Dwi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of firm size, profitability, and leverage on firm value. The design in this study is to use quantitative associative research. Data sourced from secondary data in the form of library research. The population of this study is the food and beverage sector companies that have been included in the IDX list for 2018-2020. Sampling using purposive sampling. The data that has been obtained will be analyzed using multiple linear regression techniques. But before that, a test will be carried out using the classical assumption test technique. This study shows that firm size and profitability have a positive and significant impact on firm value. Meanwhile, leverage has a negative and significant effect on firm value. Investors who want to invest in a company, especially a food and beverage company, must know and consider the company's performance and value which can be reflected in several aspects of financial ratios such as Size, DAR, ROA because these ratios can assess the level of risk of investing in shares in the company food and drink.